2004
DOI: 10.1590/s0100-06832004000200004
|View full text |Cite
|
Sign up to set email alerts
|

Frações de fósforo após extrações sucessivas com resina e incubação, em Latossolos e Luvissolos do semi-árido de Pernambuco

Abstract: RESUMOA reposição do P mais lábil pelas frações menos lábeis do solo foi avaliada após dez extrações sucessivas com resina e incubação, durante quatro meses, em amostras dos horizontes A, BA e Bw de Latossolos e A e Bt de Luvissolos, coletadas do terço superior, médio e inferior de três toposseqüências de cada classe, fazendo-se um fracionamento seqüencial de P antes das extrações sucessivas e depois da incubação. O fracionamento foi feito com resina, NaHCO 3 (fração orgânica e inorgânica), NaOH (fração orgâni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…FYM applications contributed to increases in soil pH (Galvão et al, 2008), which favor the solubilization of Fe and Al phosphates, while Ca applications promote precipitation of Ca phosphates (Lindsay, 1979). Commonly, in highly weathered soils, typical of the humid tropical region in northeastern Brazil (Ball-Coelho et al, 1993; or in the semi-arid region when originated from weathered sedimentary rocks (Tiessen et al, 1992;Araújo et al, 2004), the Al-P and Fe-P forms, extracted by NaOH, are proportionally higher than Ca-P forms (Salcedo, 2007). The opposite situation Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…FYM applications contributed to increases in soil pH (Galvão et al, 2008), which favor the solubilization of Fe and Al phosphates, while Ca applications promote precipitation of Ca phosphates (Lindsay, 1979). Commonly, in highly weathered soils, typical of the humid tropical region in northeastern Brazil (Ball-Coelho et al, 1993; or in the semi-arid region when originated from weathered sedimentary rocks (Tiessen et al, 1992;Araújo et al, 2004), the Al-P and Fe-P forms, extracted by NaOH, are proportionally higher than Ca-P forms (Salcedo, 2007). The opposite situation Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…In soils where no P was applied, Gonçalves et al (1989) observed a small, non-systematic variation of the recovered P extracted by resins, Bray-1 and Mehlich according to incubation. In a study by Araújo et al (2004), positive or negative variations of labile Pi and Po were found in fractions extracted by bicarbonate from soils incubated for 120 d. The authors attributed the effect on buffering or on the increase of the labile fraction to the moderately labile P fractions (NaOH-P). Using the ignition method, Acquaye (1963) reported that mineralization or increased Po is significantly influenced by soil physicochemical properties, soil fertilization, temperature and humidity, and incubation time.…”
Section: Percentage Distribution Of Total Inorganic (Pi) Total Organmentioning
confidence: 99%
“…Assim, os Vertissolos parecem ter pouco P retirado com os extratores mais fracos (resina e bicarbonato de Na), mas muito retirado com extratores mais fortes (hidróxido de Na e ácido sulfúrico). Faltam dados para saber se este P está disponível para as culturas, mas sabe-se que parte do P destas frações é deslocada para as frações mais lábeis, quando estas são retiradas (Araújo et al, 2004b), e isto pode justificar seu uso agrícola continuado na região.…”
Section: P Resina Pi Nahco3unclassified